Occupational stress among nurses and pre-hospital emergency staff - Rajabi, Fazel; Jahangiri, Mehdi; Molaeifar, Hossein; Honarbakhsh, Marzieh; Farhadi, Payam (Technische Universität Dortmund, 2018)
Healthcare professionals, especially nurses and pre-hospital emergency (PHE) staff, are influenced by many stressors due to their responsibility to provide comfort as well as care and treatment of patients. The aim of the present study was to identify and rank the occupational stressors in nurses and PHE staff using Fuzzy Analytic Hierarchy Process (FAHP) method. In this cross-sectional study, occupational stress factors in nurses and PHE staffs were identified and ranked by 30 experts, using FAHP method. Occupational stress factors were collected by General Health Questionnaire (GHQ), Job Stress Questionnaires as well as a literature review. Among the occupational stress factors in nurses, the highest scores were related to “Incompatibility between work schedule and life conditions” (0.03986) and “Being criticized by supervisors” (0.03723), respectively. The most common stress factors in PHE staff were related to “Care of patients with critical health conditions” (0.07258), “High number of missions” (0.07056), respectively. The overall results of this study showed that managerial factors and factors related to patient care are the most important causes of occupational stress among nurses and PHE staff. These factors should be considered in the implementation of control strategies for reducing and managing occupational stress.
application of fuzzy analytic hierarchy process (FAHP) method
EXCLI Journal;Vol. 17 2018
Keywords: Occupational stress factors; Nurses; Pre-hospital emergency staff; FAHP method; 610